Series on Multi-Centred Modernisms. Introduction. - Monica Juneja; Franziska Koch (The Journal of Transcultural Studies, 2010)
This contribution introduces a series of articles that will appear in this and the following issues of Transcultural Studies under the title "Multi-Centred Modernisms—Reconfiguring Asian Art of the Twentieth and Twenty-First Centuries".